Electronic Document Management System and Services: in Digital Perspectives - Singh, Anuj Kumar (Library Waves, 2015)
The term ‘digital’ has changed the whole scenario of systems and services. The traditional way of system and services of documents delivery and management is not in much better condition. And this is the need of the society that there must be some other type of service which can fulfill users demand as and when it is required. The society is now capable and almost they are now using the services of digital equipments. So the delivery of documents in electronic way is the present day demand of users of libraries. Not only libraries but also the whole society is moving towards this. Everyone organizes their documents, emails, scans, electronic faxes, graphics etc. in their own way and whether or not they use document management system. This paper mainly deals with the concept, situation and new technologies regarding to Electronic Document Management System (EDMS).